Penerapan Teknologi Augmented Reality Untuk Rangkuman Isi Buku Pada Perpustakaan Fakultas Berbasis Android - Aisyah Aminy Batubara; Triase; Imam Adlin Sinaga (STMIK Budi Darma, 2023)
Summary is a restatement of a long text in a more form short or concise. In a summary, trimming of a text is done by taking the main sentences and explanatory sentences that are important but not omit the idea of ??the original text. The results of research that was previously carried out on several students, Information Systems Program, where results the research 80.4% of students often have difficulty to get core information from the Information Systems Study Program textbook on It takes a while to get the substance of the book at the library of the Faculty of Science and Technology. And in order to solve this issue, planning build a technology Augmented Reality, linked in get core information from the manual for the information systems study program. Multimedia Development Life Cycle (MDLC), the relevant development methodology, was used in this study can produce applications augmented reality android-based which can display a 3-dimensional virtual form of 10 books information system lessons in the FST library and book synopsis in the form of audio so that readers can find summary information on the contents of the book. Development This application goes through several stages and involves some of the software in between architectural planning, planning storyboard, and user interface. 3D rendering model with 3D blender software and finally component assembly and manufacture augmented reality use software unity 3D